ChemInform Abstract: Zeolite Membranes — A Review and Comparison with MOFs. Issue 48 (December 2015) - Rangnekar, N.; Mittal, N.; Elyassi, B.; Caro, J.; Tsapatsis, M.
Abstract: Review: emphasis on synthesis techniques, industrial applications, hydrothermal stability, and polymer‐supported and mixed matrix membranes; 373 refs.